Hyponatremia in children of 2 months to 5 years of age with community acquired pneumonia and its correlation with severity of illness and outcome - C. K. Praneetha; Varsha Suresh Ahirrao; K. Srinivasa; R. Premalatha; Ravichander B. (Pediatric Review: International Journal of Pediatric Research, 2019)
Introduction: Hyponatremia is a common electrolyte imbalance observed in children with pneumonia. Presence of hyponatremia may increase the morbidity and mortality in pneumonia. The purpose of the study was to find the frequency of hyponatremia in 2 months to 5 years old children hospitalized with pneumonia and to correlate the hyponatremia with the severity of pneumonia.Methods: This prospective observational study involved 122 children of 2 months to 5 years, admitted in tertiary care hospital from 2016 to 2018 with community acquired pneumonia. Subjects were classified as pneumonia and severe pneumonia according to WHO criteria. Relevant demographic, clinical data and outcome of the patients were noted. Serum sodium was analyzed and was correlated with severity of pneumonia.Results: Out of 122 children included in this study, 73 were boys and 49 were girls. Hyponatremia was found in 43.5% of children with community acquired pneumonia. Mild hyponatremia was the commonest and seen in 66% children. 68% of children with severe pneumonia had hyponatremia compared to 23% children with pneumonia (p value<0.01). 48% of patients with hyponatremia compared to 26% of patients without hyponatremia had hospital stay more than 7 days which was statistically significant. Mortality was 12% in children with hyponatremia compared to 1.5% with normonatremia.Conclusion: Hyponatremia is a common electrolyte imbalance found in community acquired pneumonia and more commonly seen in severe pneumonia. Hyponatremia is associated with prolonged hospital stay and increased mortality.